Gaming as an Educational Material for Digital Competences in Education from Academic Skills Centres - García-Quismondo, Miguel Ángel Marzal; Cruz-Palacios, Eduardo (Revista General de Información y Documentación, 2018)
The competence-based educational model for 21st century Higher Education is analyzed taking into consideration how learners’ competences thrive in the multiliteracies environment. There are four main arguments for this research. Firstly, the Web, as an educational space, is an essential system to allow the generation of knowledge, and that requires the methodology of educational innovation on informational behavior, Connectivism as the ideal pedagogy on non-borders learning (anytime and anywhere), and networks as the appropriate means of the communication of knowledge. Then, digital competences are considered as a priority to framework-based permanent, cooperative learning objectives. In addition, Gaming is examined as a suitable, web, educational resource that is potentially effective on learning programs. After that, Academic Skills Centres (ASC) are reckoned as a necessary institution from which Gaming-based learning objects are managed in order that they are available for the development of educational competences programs. Finally, this research ends up proposing a competence-based program that reflects how similar, educational programs taking place in ASCs must be designed regarding their modular, progressive structure consisting of twelve didactic units, and their teaching dynamics as pedagogical methodology geared towards a greater educational effectiveness.